ISLAM DALAM BINGKAI HANIF ANALISIS PENAFSIRAN AYAT-AYAT HANIF DALAM AL-QUR’AN - rindi, Rindiandika; Fathoni , Muh Fathoni Hasyim (UIN Mataram, 2024)
Islam comes with good values and encourages people to adorn themselves with them, and instructs people to fight for and defend religious values, so that they can take the straight path (hanif). But all of that cannot be accomplished except by following the laws that have been established in Islam. In the context of the Qur'an, to indicate a straight religion is by using the word Hanif. Our guidance is to always follow the hanif millah of Ibrahim, by always monotheizing Allah and not associating partners with Him. Hanif describes a heart that is free from envy and jealousy, a heart that is inclined towards monotheism and away from shirk, a heart that loves the hereafter and can make the world as a provision for the benefit of the hereafter, a heart that is clean from desires that can prevent himself from Allah's prohibitions. Therefore, this paper will refer to the interpretation of the verses of the Qur'an that might explain the true meaning of hanif and hopefully we can all embrace the true religion of Islam and can practice and apply it in everyday life.